2021
DOI: 10.1016/j.jnlest.2021.100095
|View full text |Cite
|
Sign up to set email alerts
|

Molecules against Covid-19: An in silico approach for drug development

Abstract: A large number of deaths have been caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) worldwide, turning it into a serious and momentous threat to public health. This study tends to contribute to the development of effective treatment strategies through a computational approach, investigating the mechanisms in relation to the binding and subsequent inhibition of SARS-CoV-2 ribonucleic acid (RNA)-dependent RNA polymerase (RdRp). Molecular docking was performed to screen six naturally occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…The Lipinski rule does not recommend more than one violation of an orally bioactive molecules. The ADME results obtained from the calculations revealed that all values obtained for compounds remained within the defined limits as specified in Lipinski's RO5 (Bharti & Shukla. 2021;Kouznetsov.…”
Section: In-silico Adme Findingsmentioning
confidence: 68%
“…The Lipinski rule does not recommend more than one violation of an orally bioactive molecules. The ADME results obtained from the calculations revealed that all values obtained for compounds remained within the defined limits as specified in Lipinski's RO5 (Bharti & Shukla. 2021;Kouznetsov.…”
Section: In-silico Adme Findingsmentioning
confidence: 68%
“…The in silico approaches, such as docking, is well-regarded and validated for predicting new drug-target associations. Several computational studies are reported on the virtual drug repurposing screening and prediction of potential drug-like occurring molecules against SARS-CoV-2; however, many of them explore natural or other molecules known in the literature [ 80 82 ]. MSC-derived EVs were known to contain miRNAs that are being investigated for their role in the progression, diagnosis and treatment of various diseases [ 83 ].…”
Section: Stem Cell-derived Extracellular Vesicles In Covid-19 and Acu...mentioning
confidence: 99%
“…Docking findings have conclusively demonstrated ligand binding to the SARS-CoV-2 RdRp protein. These findings give a rationale for repurposing and employing compounds derived from plants and animals as prospective treatments for the coronavirus disease 2019 (COVID-19) infection, since they may be effective therapies for the same [ 63 ].…”
Section: Phytomedicine Identified By Computer-aided Drug Design (Cadd...mentioning
confidence: 99%
“…Rutin (24) and Nicotiflorin (25) are glycoside flavonoids found in various medicinal plants and ayurvedic tea [ 63 ]. Rutin Hydrolysis Quercetin and other human metabolites have antioxidant, anti-inflammatory, and antiviral characteristics that contribute to a healthy diet.…”
Section: Phytomedicine Identified By Computer-aided Drug Design (Cadd...mentioning
confidence: 99%